Optimization of the Kring Serse of the Surakarta Police in Preventing the Event of 3C for the Realization of Harkamtibmas - Muhammad Rayhan Rasendruya Natasaputra (Advances in Police Science Research Journal, 2022)
The final project, entitled Optimizing the Kring Serse of the Surakarta Police in preventing the occurrence of 3C in order to realize Harkamtibmas, discusses the increase in incoming reports related to criminal acts of 3C even though the Kring Serse has been carried out at the Surakarta Police. As for the background of the writing of this final project, namely the implementation of the Kring Serse which has not been optimal by the Surakarta Police Criminal Investigation Unit. The purpose of writing this final project is to find out the system and method of implementing the Kring Serse, the capabilities required by the Criminal Investigation Unit, and collaboration with various related parties to prevent 3C cases. The research method used qualitative research method with data analysis techniques using interview techniques, observation, and then concluded through a comprehensive analysis. The theoretical basis used is management theory, competency theory and cooperation theory, so that it is hoped that it will be able to optimize the security of the Surakarta Police Criminal Investigation Unit in preventing 3C. The conclusion in this final project are to improve the management process in the aspects of human resources, budget, facilities, and methods. Then, it is also necessary to increase the ability of the Sat Reskrim personnel in carrying out the Serse Service and the need to collaborate with various parties, both internally and externally to optimize the Serse Service at the Surakarta Police to prevent 3C in realizing Harkamtibmas.